2022
DOI: 10.3390/bioengineering9100555
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Spatiotemporal Control in Vascularized Tissues

Abstract: A major challenge in engineering scalable three-dimensional tissues is the generation of a functional and developed microvascular network for adequate perfusion of oxygen and growth factors. Current biological approaches to creating vascularized tissues include the use of vascular cells, soluble factors, and instructive biomaterials. Angiogenesis and the subsequent generation of a functional vascular bed within engineered tissues has gained attention and is actively being studied through combinations of physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 132 publications
0
14
0
Order By: Relevance
“…Several methods have been developed to replicate this process by incorporating growth factors into biomaterials to manage vascular growth and development in vitro. The signaling proteins that predominantly affect angiogenesis are vascular endothelial growth factor (VEGF), acidic fibroblast growth factor (aFGF), and basic fibroblast growth factor (bFGF) [ 140 ]. Son et al mapped the topography of the growth factor gradient using growth factor-secreting cells.…”
Section: Characteristic Control Of Microvascular Networkmentioning
confidence: 99%
“…Several methods have been developed to replicate this process by incorporating growth factors into biomaterials to manage vascular growth and development in vitro. The signaling proteins that predominantly affect angiogenesis are vascular endothelial growth factor (VEGF), acidic fibroblast growth factor (aFGF), and basic fibroblast growth factor (bFGF) [ 140 ]. Son et al mapped the topography of the growth factor gradient using growth factor-secreting cells.…”
Section: Characteristic Control Of Microvascular Networkmentioning
confidence: 99%
“… 83 They allow enough time to form neo matrix and progressive re-assimilation via protease activity. 84 Fibrin can be employed as a biological framework with other elements to regenerate primary cells, skin, bones, and so on. 85 Nevertheless, it has the disadvantage of quick degradation, which makes it unsuitable for creating particular scaffolds.…”
Section: Polymeric-based Biomaterialsmentioning
confidence: 99%
“…It has also been demonstrated that EVs contribute to the increase of drug resistance of cancer cells [ 146 ]. On the other hand, signaling proteins have been mentioned regarding the vascularization of scaffolds and tissue models [ 147 ].…”
Section: Scaffolds For Mimicking Breast Cancer Tissue Microenvironmentmentioning
confidence: 99%